Analysis and forecasting of the dynamics of the gross domestic product per capita by purchasing power parity in Russia - M. O. Govallo; D. D. Lobanova; L. A. Davletshina (Вестник университета, 2025)
This article provides an extensive analysis of the dynamics of gross domestic product (hereinafter referred to as GDP) per capita by purchasing power parity in the Russian Federation (hereinafter referred to as RF, Russia) for the period from 1995 to 2022. Using exponential smoothing and an adaptive forecasting method, the indicator forecast is built for the period from 2023 to 2027. The characteristic and description of the mathematical and statistical models used are given. The reasons for choosing the model are determined and justified. Based on the results of the calculations, the paper evaluates the forecast indicators and draws conclusions about forecasting the GDP in Russia. It is concluded that the chosen model accurately reflects future changes in the indicators and suggests that the developed strategies and plans based on these forecasts can be successfully implemented. The article also mentions the influence of a random component caused by unpredictable factors on the final results. The opinion of other persons regarding the GDP forecast in Russia has also been studied. The results of the conducted research and conclusions drawn can become valuable material for further study for economists and governing bodies at various levels.